Preparation and performance of composite agent with anti-seepage and friction reducing for pipe jacking in water-rich sand stratum - Hairong Gu; Kai Wu; Peng Zhang; Jiejun Yuan; Xiao Zhang; Kui Shi (PLoS ONE, 2026)
Pipe jacking in water-rich sandy strata is frequently suffered by rapidly increasing seepage-induced hazards (e.g., groundwater inrush at working shafts) in jacking lubrication, which is because their limited anti-seepage capacity of conventional bentonite-based lubricants. In order to enhance the lubrication and anti-seepage performance of lubricants along the pipe–soil annulus, this study developed a composite agent with anti-seepage and friction reducing, where graphite(SM) is used as lubrication, Na 2 CO 3 is used as dispersibility, polyacrylamide(PAM) is used as thixotropy, polyisocyanates and polyols are used as primary agents, triethanolamine(TEA) and dibutyltin dilaurate (DBTDL) are used as catalysts, and sodium silicate is used as water resistance due to the gelation effect at lower temperatures. The preparation method of the composite anti-seepage and friction reducing agent was investigated, and its macro- and micro-scale performance tests were conducted. Additionally, the optimal mix ratio was determined using the range analysis method and entropy weight method. The research indicates that the optimized composition of the composite anti-seepage and friction reducing agent is as follows: SM(0.8%−1.0%), PAM (2.0%−2.5%), Na 2 CO 3 (0.3%−0.5%), DBTDL (1.4%−1.6%), TEA(1.0%−1.5%), and Na 2 O·3.1SiO 2 (15%−20%). Compared to traditional bentonite-based friction reducing agent, the funnel viscosity range is reduced by 55%, the filtration loss range is reduced by 25%, the water separation rate is decreased by 4.5% (approaching 0), the friction coefficient is lowered by 20% ~ 28%, and the permeability coefficient reaches 3.5 × 10 - ⁵-5.0 × 10 - ⁵ cm/s. This paper addresses the issues of high frictional resistance and difficult waterproofing in jacking construction through water-rich sand stratum. The proposed preparation process of composite agent provides an essential material of practical route for reducing jacking forces and eliminating water inrush risks during pipe jacking in water-rich sandy strata.